2022
DOI: 10.3390/biomedicines10020455
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Hidradenitis Suppurativa during Biologic Therapy, an Emerging Challenge: A Systematic Review

Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease usually occurring after puberty with painful, deep-seated, inflammatory lesions in the apocrine gland-bearing areas of the body. Although HS pathogenesis is still unproven, recent major research advantages have increased our knowledge of the mechanisms behind HS lesions. Particularly, follicular occlusion followed by follicular rupture has been shown to be crucial to HS development, leading to immune response activation, and resulting in typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Indeed, patients affected by both diseases require personalized therapies and continuous follow-up. [20][21][22][23][24] As regards acne, several studies have been reported. Indeed, acne was the main field of application of telemedicine during the pandemic and the use of this tool for acne management has been investigated also before COVID-19 period.…”
Section: Teledermatology Acne and Hidradenitis Suppurativamentioning
confidence: 99%
“…Indeed, patients affected by both diseases require personalized therapies and continuous follow-up. [20][21][22][23][24] As regards acne, several studies have been reported. Indeed, acne was the main field of application of telemedicine during the pandemic and the use of this tool for acne management has been investigated also before COVID-19 period.…”
Section: Teledermatology Acne and Hidradenitis Suppurativamentioning
confidence: 99%
“…The above-mentioned treatments have a positive effect on the reduction of acne lesions, reduction of the level of sebum on the surface of the epidermis, and improvement of skin hydration [ 25 , 26 ]. We hope that our research results and the treatments that we have proposed, can be used by other researchers to apply them to another disease, for example hidradenitis suppurativa [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, IL-23 has been showed to regulate T-cells production of high IL-17, resulting in a self-amplifying inflammatory response in keratinocytes, and finally in the development of typical psoriasis. [93][94][95][96] In this context, recent major research advancements resulted in the development of new biological drugs specifically inhibiting the key function played by IL23. 97 Anti-IL23 drugs (guselkumab, risankizumab, and tildrakizumab) represent the latest class of biologics approved in the treatment of moderate to severe psoriasis.…”
Section: Anti-il23mentioning
confidence: 99%